4 Refining pathologic interpretation of endometrial carcinomas: lessons learned from a nationwide study in a new era of molecular classification. (13th November 2020) - Thompson, E; Huvila, J; Leung, S; Irving, J; van der Westhuizen, N; Kinloch, M; Lytwyn, A; Sur, M; Parra-Herran, C; Yasmeen, A; Gougeon, F; Morin, C; et al.
Abstract : Objectives: Molecular classification of endometrial carcinoma (EC) enables consistent classification of tumours and provides valuable prognostic and predictive information. Herein we describe molecular subtype distribution and histomorphologic correlates in recently diagnosed (2016) ECs from across Canada. Methods: Molecular classification was performed on representative tumour specimens from participating centres. Clinicopathologic, management and outcome data were collected (REDCap). Results: 1453 ECs from 30 centres have been identified. Complete molecular (ProMisE) and outcome data is reportable for 862 patients. Histologic and clinicopathologic parameters associated with molecular subtype and are summarised in table 1 . Amongst participating centres, routine testing of MMR and p53 immunohistochemistry (IHC) was performed in only 23.5% (range 3.5–80.0% per centre) and 15% (2.2–45.7%) of cases respectively. We found p53 abn ECs across a range of histotypes, including low grade endometrioid EC. Subclonal p53 staining was observed in 3.9% of cases and significantly associated with the presence of pathogenic POLE mutations (p≤0.001). Subclonal MMR IHC expression was seen in 3.5% of cases and has previously been shown to occur predominantly in the context of MLH1 hypermethylation. MMRd was significantly associated with LVI (p <0.001). ProMisE subtype was significantly associated with clinical outcomes (p<0.001) even in low stage disease [OS p=0.045, DSS p=0.009, PFS p=0.005 for stage I]. Conclusions: Observation of unusual or unexpected p53 and MMR IHC staining patterns and associated clinical implications highlight the importance of routine testing of these parameters in ECs.